EVALUATION OF BRT SERVICE PERFORMANCE IN SEMARANG CITY. Case Study : Corridor II, Ungaran - Terboyo - Aldila Bachtawar Zardari; Ilham Hussein Rasyid; Ismiyati Ismiyati; Bambang Riyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Public Transport is one of the solutions to resolve the traffic in urban area, particularly in Semarang City. Therefore, Semarang City Government provided the public transports in the form of Bus Rapid Transport (BRT) Corridor I (the route of Mangkang – Penggaron) and Corridor II (the route of Ungaran – Terboyo Bus Station). According to the service performance evaluation to BRT Corridor I by Adyan and Salman in 2012, it was found that the Load Factor was 44,73%, and it did not meet the standard of PP.No.41/1993 and SK. Dirjen no.687 stating that the minimum load factor is 70%. Though the service provided was better than other public transportation. Therefore, an evaluation is required to the service performance on BRT Corridor II to determine whether BRT corridor II has the same problem as BRT Corridor I and how the solution to be used as a reference to the next corridor. This research applied the methodology of Dynamic Survey on BRT, Static Survey, Origin Destination Survey and Home Base Survey. Based on the survey and analysis results, it was obtained that the Load Factor by 23.51% is below the standard. In conclusion, the service performance of BRT Corridor I and BRT Corridor II was experiencing the same problem from the aspect of efficiency and effectiveness which is in accordance with the applicable standards but it was found in the field that the load factor was less than 70%. Based on the Home Base Survey, the non-users who are around BRT Route suggested that the manager should be more intensive in socializing BRT to communities and pay attention on the punctuality of BRT travel time. There are still a lot of transport other than BRT operating on the same route, which also resulted in a lack of BRT Load Factor because people tend to choose the transport that can stop anywhere, and it is in contrary with the purpose of the Public Transport. The researcher suggested that BRT and public transports other than BRT are under one management in terms of all the transportations stop in the shelters and have the same service standard. According to survey and analysis, Route from Ungaran to Pemuda and Raden Patah to Ungaran use BRT, whereasPemuda to Terboyo and Terboyo to Raden Patah use feeder transport in other to minimalize cost and make time around become quick, and according to analysis load factor from corridor I and II, prove BRT not too effective presents in Semarang City.